The Use of Phet Simulations to Improve High School Students’ Understanding of Physics Concepts: A Systematic Literature Review - Maria Anastasia Da Lopez; Ziadatun Nikmatillah; Alia Cahyani; Gunawan Gunawan; Nina Nisrina (Indonesian, 2023)
The use of technology-based learning media, particularly PhET (Physics Education Technology) simulations, is widely adopted in high school physics education. PhET provides interactive simulations capable of visualizing abstract physics concepts, thereby facilitating a better understanding of the material for students. Various studies indicate that the integration of PhET can enhance conceptual understanding, learning outcomes, and student engagement in the learning process. This study aims to analyze research trends regarding the use of PhET in improving high school physics conceptual understanding during the 2014–2023 period, providing a comprehensive overview of literature development over the past decade through a Systematic Literature Review (SLR) approach. Data were gathered from relevant academic databases and analyzed to identify the growth in publication numbers, author collaboration patterns, and dominant research topics. The results show a steady increase in PhET-related publications over the years. Frequently researched topics include conceptual understanding, learning outcomes, critical thinking skills, and technology-based learning. Furthermore, PhET has proven effective in helping students grasp complex physics concepts through interactive visualization. In conclusion, research on PhET displays an upward trend and contributes positively to improving the quality of physics education at the senior high school level. This study is expected to serve as a valuable reference for developing innovative and effective learning media